Synthesis of 5-phenyl-1,8-naphthalic anhydrides: An exercise in acenaphthene chemistry (2024)
ABSTRACT: The synthesis of phenylnaphthalic anhydrides, including substitution patterns typically found in the Haemodoraceae and Pontederiacea family of plants, was explored using Suzuki and Ullmann-type aromatic substitutions on acenaphthene. Synthetic challenges were surmounted by tactical changes to determine the order of events.